2022
DOI: 10.2464/jilm.72.593
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the role of Sn on negative effect in two-step aging in an Al-Mg-Si alloy by XAFS analysis

Abstract: Al-Mg-Si 合金は強度と加工性のバランスに優れた合金であ り,近年自動車ボディパネル材への適用が進んでいる 1), 2) 。 自動車ボディパネルの製造工程では,本合金板材の溶体化処 理ならびに焼入れを行い,その後プレス成形および焼付塗装 熱処理(443 Kで1.2-3.6 ks 間)が行われる。溶体化処理はア ルミニウムメーカー,プレス成形および焼付け塗装は自動車 メーカーで施されるため 3) ,焼入れ後から焼付塗装熱処理を 施すまでの間,輸送等により本合金は一定期間室温で保管さ れる。本合金は析出強化型合金であり,焼入れ後直ちに 443 K 時効を施すと,強化相であるβ" 相が析出し硬度が著しく増 大する。しかし,焼入れ後の室温放置により,焼付塗装熱処 理時に時効硬化量が著しく減少する「二段時効の負の効 果」 4) 8) が生じ,実用上の問題となっている。この原因とし て,自然時効(以後,NA)中に形成されたクラスタが,後の 443 K 時効でβ" 相の析出を阻害するためと考えられてい る 2), 6), 9) 12) 。よって,NA中に形成されるクラスタを抑制する ことが求められる。 過去の報告 13) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…In this study, the formation of clusters in Al-1.04 mass%Si-0.55 mass%Mg alloys at the early stages of natural aging was investigated by soft X-ray XAFS measurements and first principles calculation. [28][29][30] XAFS measurements near the Mg-K and Si-K edges were carried out at the BL27SU beamline at SPring-8. It was found that the absorption edge energies changed with aging as shown in Fig.…”
Section: Dtimentioning
confidence: 99%
“…In this study, the formation of clusters in Al-1.04 mass%Si-0.55 mass%Mg alloys at the early stages of natural aging was investigated by soft X-ray XAFS measurements and first principles calculation. [28][29][30] XAFS measurements near the Mg-K and Si-K edges were carried out at the BL27SU beamline at SPring-8. It was found that the absorption edge energies changed with aging as shown in Fig.…”
Section: Dtimentioning
confidence: 99%